2008
DOI: 10.1007/s10552-008-9126-9
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer care knowledge mapping: identifying priorities for knowledge translation research

Abstract: Several opportunities were revealed for improving the quality of CRC screening and surgery. Greater coordination of, and support for KT research is required to address these gaps. Further research should evaluate different methods of achieving KT between researchers and decision makers for research planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 140 publications
2
3
0
Order By: Relevance
“…However, the data presented hints that the former may be the situation since acquisition of resistance correlated better with loss of POU5F1 rather than NANOG in the NT2-NANOG cells with increasing RA treatment. This would be consistent with the recent findings of Gutekunst et al [6] who showed that POU5F1 expression is essential to provide the pro-apoptotic environment needed to maintain drug sensitivity in undifferentiated NT2-D1 cells.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, the data presented hints that the former may be the situation since acquisition of resistance correlated better with loss of POU5F1 rather than NANOG in the NT2-NANOG cells with increasing RA treatment. This would be consistent with the recent findings of Gutekunst et al [6] who showed that POU5F1 expression is essential to provide the pro-apoptotic environment needed to maintain drug sensitivity in undifferentiated NT2-D1 cells.…”
Section: Discussionsupporting
confidence: 93%
“…Mueller et al [33] previously reported that loss of POU5F1 expression induced by differentiating GCT cell lines with a medium containing fetal bovine serum and steroids resulted in cDDP resistance, and this has been confirmed by knockdown of POU5F1 [6]. This is consistent with other studies reporting that differentiation of embryonal carcinoma cells leads to induction of resistance [20].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Academic family medicine departments are increasingly recognizing the importance of educational research and are creating support structures for its advancement. Researchers have advocated for the development of programs of research rather than the conduct of single studies [ 16 , 17 ]. Regehr [ 5 ] noted that there is a distinction between scholars working on the same topic and scholars working toward a shared goal.…”
Section: Introductionmentioning
confidence: 99%
“…Most strategies are not routinely applied outside of experimental studies and few program evaluations are published which would provide information about the impact and implications of these strategies in a variety of contexts. By systematic review we found no studies evaluating implementation of breast cancer management guidelines [23], and only two studies evaluating implementation for colorectal cancer management guidelines [24]. Therefore, little data about cost and contextual effectiveness is available to guide decisions about which implementation strategies are most useful in the real world.…”
Section: Introductionmentioning
confidence: 99%